Criminology of Cases of Children as Perpetrators of Bullying That Lead to Criminalization - Wiwik Aswanti; Laksanto Utomo; Joko Sriwidodo (Greenation Research & Yayasan Global Resarch National, 2024)
Acts of bullying committed by children often lead to criminal acts, if the bullying is not immediately known and controlled by other parties. The bullying that is often carried out by children against their friends is triggered by various things. Criminal acts committed by children certainly cannot be equated with criminal acts committed by adults. The role of criminology is very important to find out the cause of a person committing a crime and criminology can also find out how to overcome the problem of these crimes. Behind it all, of course, the role of family, peers, teachers and the environment is very influential.